Consumer drones and communication on the fly. (September 2019) - Hildebrand, Julia M.
In this article, I discuss camera drones as mobile media that help access, collect, and shape physical, digital, and social spaces. As such, consumer drones afford "communication on the fly" in their medium-specific configuration of aerial navigation, visual production, and networked communication. Drawing on in-depth interviews with drone users and auto-ethnographic drone practices, I first highlight what physical-material conditions the flying camera mediates. An analysis of what digital-intangible formations the sensor medium collects and creates follows, before I turn to the sociospatial relations the buzzing mobile interface can establish and disrupt. I show how these conditions of communication on the fly shape user practices of place-sensing and place-making. Through the lenses of mobile communication research, media ecology, and mobilities studies, I ultimately illuminate how the ambiguous aerial system helps expand our thinking of and with notions of communication on the move.